Shared learning for oral health therapy and dental students: enhanced understanding of roles and responsibilities through interprofessional education. (28th May 2012) - Ritchie, C.; Dann, L.; J Ford, P.
Abstract: Introduction: To enhance interprofessional learning outcomes, The School of Dentistry at The University of Queensland redesigned first‐year curricula. Courses for Bachelor of Oral Health (OHT) and Bachelor of Dental Science (DS) students were combined, and learning content created to support the development of skills, knowledge and attitudes required for the oral healthcare team to work effectively in providing the best possible care for patients. Methods: Over a 2‐year period, all commencing OHT and DS students were invited to participate in this study. One cohort ( n = 93) was enrolled into a traditional, discipline‐specific programme (TRAD), whereas the other cohort ( n = 93) experienced an integrated learning programme (INT) with combined courses for OHT and DS students. The Readiness for Interprofessional Learning Scale (RIPLS) and a modified dental and dental care professional roles and responsibilities (DRR) survey were completed to determine students' awareness of dental professionals' roles and responsibilities, and their attitudes to interprofessional education and teamwork. Results: Following completion of 1 year of learning, both INT and TRAD cohorts showed similar levels of readiness for shared learning. At the commencement of the second year of the study programme, however, there was a significantly better understanding of shared care amongst INT students. Conclusions: This study provides initial support for the integrated learning approach adopted by this university. The INT cohort had significantly improved understandings of the roles and responsibilities of dentists and oral health therapists. The results of this study have been used to refine ongoing curriculum developments.